13th World Congress of Food Science &Amp; Technology 2006
DOI: 10.1051/iufost:20060337
|View full text |Cite
|
Sign up to set email alerts
|

Grape skin and seeds hardness assessment by texture analysis

Abstract: In order to optimize wine quality it is important to first characterize grape phenolic maturity and to determine the extractability of phenolic compounds during winemaking. The choice of harvest date is therefore very important but nevertheless still empirical. Previous works showed the interest of grape texture measurement as factor of grape maturity characterization. This work proposes to focus on berry skins and seed texture properties of three grapevine varieties: Cabernet sauvignon, Pinot noir and Nebbiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
2
0
2
Order By: Relevance
“…The force was recorded every 0.33 s. Each specimen was placed on a flat steel holder (10 mm thick) with a hole (10 mm in diameter) in the center and was penetrated on the equatorial side (perpendicular to the abscission zone). This appears to be the best position for grape puncture test as supported by previous studies by Lee and Bourne (1980) and Letaief et al (2006). From the forcedisplacement curve, three mechanical parameters were computed.…”
Section: Evaluation Of Mechanical Propertiessupporting
confidence: 54%
See 1 more Smart Citation
“…The force was recorded every 0.33 s. Each specimen was placed on a flat steel holder (10 mm thick) with a hole (10 mm in diameter) in the center and was penetrated on the equatorial side (perpendicular to the abscission zone). This appears to be the best position for grape puncture test as supported by previous studies by Lee and Bourne (1980) and Letaief et al (2006). From the forcedisplacement curve, three mechanical parameters were computed.…”
Section: Evaluation Of Mechanical Propertiessupporting
confidence: 54%
“…The authors concluded that, after ripeness, skin strength and elasticity dropped severely, and the loss of cell wall polysaccharides was compensated by the inclusion of structural proteins. Letaief, Rolle, Zeppa, and Gerbi (2006) focused their interest on grape texture measurement as a grape maturity index, and reported not significant differences between berries picked from different bunch positions.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Hankinson et al (1977), a resistência à compressão está ligada à coesividade entre as células da epiderme, enquanto a resistência à perfuração está relacionada ao tamanho destas células. Letaief et al (2006) obtiveram valores de força de perfuração para as cultivares Cabernet Sauvignon (0,46 N),Pinot Noir (0,50 N) e Nebbiolo (0,35 N). Fava et al (2011) encontraram valores de 4,9 N para força máxima de perfuração da cultivar Isabel, superior ao obtido no presente trabalho, porém utilizaram uma sonda de três milímetros de diâmetro com ponta de seção plana e não do tipo agulha, o que pode ter provocado um efeito parcial de compressão.…”
Section: Resultsunclassified
“…Yamamoto e Satoh (1994) adaptaram para videira um método descrito por Verner e Blodgett (1936) para cerejas, determinando o índice de rachamento por imersão das bagas de uva em água destilada. Outros autores avaliaram a relação do rachamento com aspectos histológicos (HANKIN-SON et al, 1977), estruturais (CONSIDINE, 1981(CONSIDINE, e 1982MATTHEWS et al, 1987) e mecânicos (CON-SIDINE; KRIEDEMANN, 1972;LETAIEF et al, 2006). Existem poucos trabalhos de determinação da sensibilidade ao rachamento das principais cultivares de uva para processamento produzidas no Brasil (YAMAMOTO; SATOH, 1994;FAVA et al, 2011).…”
Section: Introductionunclassified
“…However, during sensory evaluation seed bitterness may be overwhelming and though distinguishing levels of bitterness / harshness may not be possible. Similarly, seed crushability (hardness) even though is a good indicator of grape maturity (Letaief et al, 2006) it is difficult to define obvious differences especially in the latter stages of fruit ripening.…”
Section: Berry Physical Attributesmentioning
confidence: 99%